Characterizing exposure to physical risk factors among reforestation hand planters in the Southeastern United States. (January 2018) - Granzow, Robert F.; Schall, Mark C.; Smidt, Mathew F.; Chen, Howard; Fethke, Nathan B.; Huangfu, Rong
Abstract: Low back and neck/shoulder pain are commonly reported among reforestation hand planters. While some studies have documented the intensive cardiovascular demands of hand planting, limited information is available regarding exposures to physical risk factors associated with the development of musculoskeletal disorders (MSDs) among hand planters. This study used surface electromyography (EMG) and inertial measurement units (IMUs) to characterize the muscle activation patterns, upper arm and trunk postures, movement velocities, and physical activity (PA) of fourteen Southeastern reforestation hand planters over one work shift. Results indicated that hand planters are exposed to physical risk factors such as extreme trunk postures (32.5% of time spent in ≥45° trunk flexion) and high effort muscle exertions (e.g., mean root-mean-square right upper trapezius amplitude of 54.1% reference voluntary exertion) that may place them at increased risk for developing MSDs. The findings indicate a need for continued field-based research among hand planters to identify and/or develop maximally effective interventions. Highlights: Hand planters are frequently exposed to extreme postures and movement velocities. Forceful exertions were common and often exceeded those observed in other industries. Hand planters have few opportunities for rest and recovery. Additional research is needed to develop new planting tools and interventions.